Using Love Song in Teaching English for Senior High School Students - Siti Hardianti; Don Narius (Universitas Negeri Padang, 2018)
Abstract English is the important language that has to be mastered. There are four skills in language learning; listening, speaking, reading, and writing. Speaking is one of language skills which is very important to be mastered by students. However, students still find some difficulties in speaking, such as vocabulary, pronunciation, grammar, and motivation. Therefore, teacher should select the appropriate media that can solve all the problems. Love Song is chosen by the writer as the appropriate media since it can solve all the problems faced by students. In using Love Song, the teacher plays a song and asks the students to play the missing lyrics game. After that, students find the meaning of the song. Then, teacher explains the material (simple present tense), and teacher asks students to find out the simple present tense in the lyrics of Everything I do (I do it for you). Next, students are given an individual task to memorize the song. After doing the individual task, the teacher asks students about the moral value of the song. The last, teacher gives homework to memorize another love song and conclude the lesson with the students. By using love song in English class, teaching and learning process will be fun and interesting. The purpose of this paper is to explain how to use Love song in teaching English for Senior High School students. Key Words: English, Speaking, Love Song, Senior High School Students